2002
DOI: 10.1001/archotol.128.9.1096
|View full text |Cite
|
Sign up to set email alerts
|

Failed Extraction of a Sharp Esophageal Foreign Body With a Flexible Endoscope

Abstract: Several methods for the extraction of esophageal foreign bodies have been described. The most common approaches use either the flexible fiberoptic esophagoscope or the rigid esophagoscope. We report an unusual complication following the attempted extraction of a sharp esophageal foreign body with a flexible esophagoscope, review the indications for these 2 methods of extraction, and discuss the potential morbidity and mortality of these 2 approaches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…30 The rigid esophagoscopy success rates range from 94% to 100%; the estimated incidence of esophageal or pharyngeal perforation is 0.34%, and mortality is 0.05%. 31,32 In the present case, rigid esophagoscopy was used and the broken head of the mirror was successfully removed.…”
Section: Discussionmentioning
confidence: 85%
“…30 The rigid esophagoscopy success rates range from 94% to 100%; the estimated incidence of esophageal or pharyngeal perforation is 0.34%, and mortality is 0.05%. 31,32 In the present case, rigid esophagoscopy was used and the broken head of the mirror was successfully removed.…”
Section: Discussionmentioning
confidence: 85%
“…The dentures' large size, sharp edges, and metal clasps make endoscopic extraction unsafe. 9 The risk of esophageal perforation is about 23%. 10 It is therefore suggested that the safest and the most effective method of removing impacted dentures in the esophagus is through an elective open esophagotomy.…”
Section: Discussionmentioning
confidence: 99%
“…These methods include the Foley catheter [11,12], glucagon [13,14], bougienage technique [15], flexible esophagoscopy [16][17][18][19], and rigid esophagoscopy [20][21][22].…”
Section: Methods Of Foreign Body Removalmentioning
confidence: 99%
“…The range of foreign bodies able to be removed with a flexible gastroscope has expanded with the development of newer snares, cages, and forceps. Removal of a foreign body with the flexible gastroscope is more likely to be successful and atraumatic when the foreign body does not have sharp or penetrating edges [19]. Flexible endoscopy, in properly trained hands, is therefore a safe and viable method for extraction of foreign bodies of the esophagus.…”
Section: Methods Of Foreign Body Removalmentioning
confidence: 99%
See 1 more Smart Citation